Pengaruh Manajemen Komunikasi Politik terhadap Keberhasilan Kampanye Digital - Diah Fatma Sjoraida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Regional Head Election in Sumedang Regency carries out campaign or political communication activities by preparing political communication management. The four candidates carried out political communication via social media with several successful teams from the four Sumedang Regional Election candidates. Candidate pair number 2 won with 313,117 votes or around 49.49% of the vote. By gaining votes from social media through Gen Z and millennials, most of whom are social media users. The couple only received 46% of the vote, while the remaining 54% were Generation X voters and the elderly generation. This makes the implementation of political communication management ineffective because political communication via social media does not bring much increase in votes from millennials in Sumedang Regency who are still not politically literate. The aim of this research is to find out and analyze the extent to which the message delivery strategy and political communication ethics of the Sumedang Regent candidate influence the success of digital campaigns on social media. The research method uses quantitative descriptive methods with data collection techniques using observation, questionnaires and literature studies, while data analysis uses data quality tests, classical assumption tests, multiple linear regression tests and hypothesis tests. According to the research results, only the political communication ethics variable (X2) partially influences the success of the digital campaign (Y), while the simultaneous results of the message delivery strategy variable (X1) and the political communication ethics variable (X2) have a very strong influence on the digital campaign success variable (Y).